Photoelectric memory in 6H-SiC - Duisenbaev, M. (Functional Materials, 2004)
In the investigated structures, the phenomenon of photoelectric memory is observed connected with the increase of a dark current by about 3 decimal orders and retained for a long time after the structure illumination with light of E = 3 eV energy at T = 300 K. The current-voltage characteristic is I ~ Vn, where n = 4.3. Optical and temperature quenching of photoconductivity were observed. Within a narrow range of light intensity, the lux-current characteristic shows a superlinear dependence with к = 4 then passing into a sublinear one with к = 0.7. The observable maximum relaxation time of residual conductivity is т = 5-104 s. Under illumination with light of energy E = 1.1 to 2 eV, the structure exhibits a sharp reduction of т. As the voltage applied to the structure increases, т decreases.